2018
DOI: 10.1002/cctc.201701317
|View full text |Cite
|
Sign up to set email alerts
|

A Bunch‐like Copper Oxide Nanowire Array as an Efficient, Durable, and Economical Catalyst for the Methanolysis of Ammonia Borane

Abstract: The dehydrogenation of ammonia borane (AB) is an effective method to produce and store hydrogen, but efficient, durable, and low‐costing dehydrogenation catalysts are lacking. In this work, we successfully prepared a self‐supported bunch‐like copper oxide nanowire array on copper foam (b‐CuO NA/CF) through a facile in situ wet oxidation and annealing method. b‐CuO NA/CF shows high catalytic activity for the methanolysis of AB with an initial turnover frequency of 13.3 molnormalH2  molCuO−1 min−1 and an activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Among them, ammonia borane (NH 3 BH 3 , AB) is considered to be an efficient carrier, with superb stability in aqueous and methanol solutions, a high volumetric density of 146 g L −1 , and a hydrogen capacity of 196 g kg −1 . Hydrogen stored in AB can be released by either thermal decomposition or solvolysis . Considering the high energy input of thermal decomposition (>100 °C), much research has been focused on the hydrolytic dehydrogenation of AB [Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, ammonia borane (NH 3 BH 3 , AB) is considered to be an efficient carrier, with superb stability in aqueous and methanol solutions, a high volumetric density of 146 g L −1 , and a hydrogen capacity of 196 g kg −1 . Hydrogen stored in AB can be released by either thermal decomposition or solvolysis . Considering the high energy input of thermal decomposition (>100 °C), much research has been focused on the hydrolytic dehydrogenation of AB [Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Since then, more and more researchers have studied the catalysts for hydrogen production from AB methanolysis, and a large number of research results have been reported. In the study of AB methanolysis for hydrogen production, the main focus is on the study of active metal and support of high activity catalyst, optimization of the catalytic hydrogen production system, and so on. …”
Section: Hydrogen Production From Catalytic Ammonia Borane Methanolysismentioning
confidence: 99%
“…278 After that, bunch-like copper oxide nanowire arrays on copper foam (b-CuO NA/CF) were prepared via a simple oxidation process and they behaved as efficient pre-catalysts (13.3 min −1 ) for methanolytic dehydrogenation of NH 3 BH 3 . 279 Recently, Sun's research group found that CuNi alloy NPs deposited on graphene (CuNi/G) showed excellent catalytic activity (49.1 min −1 ) and recyclability toward the methanolysis of NH 3 BH 3 . 280 More recently, a noble-metal-free Cu/Co(OH) 2 nanohybrid pre-catalyst was fabricated by Chen and coworkers via a feasible in situ method.…”
Section: Catalysts For Nh 3 Bh 3 Methanolysismentioning
confidence: 99%